Electrochemical device and electronic device

By using high tensile strength elements and controlling specific weight and density in the negative electrode current collector and active material layer of lithium-ion batteries, combined with specific electrolyte composition, the insufficient expansion performance of lithium-ion batteries during high temperature and cycle use is solved. problem, significantly improving the high-temperature storage and cyclic expansion performance of electrochemical devices.

CN119340335APending Publication Date: 2025-01-21NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411454169.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2020-10-15
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the high temperature conditions and during the recycling process, existing lithium-ion batteries have problems such as insufficient storage expansion performance and cyclic expansion performance.

Method used

By doping the negative electrode current collector with elements with high tensile strength, such as copper, silver or tin, and controlling the specific weight and density in the negative electrode active material layer, combined with the specific electrolyte composition, the performance of the electrochemical device can be improved. High temperature storage expansion performance and cyclic expansion performance.

Benefits of technology

Significantly improves the high-temperature storage expansion performance and cycle expansion performance of lithium-ion batteries, prevents the negative electrode from breaking, and fully utilizes the capacity of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005089986130000021
    Figure BDA0005089986130000021
  • Figure BDA0005089986130000023
    Figure BDA0005089986130000023
  • Figure BDA0005089986130000031
    Figure BDA0005089986130000031
Patent Text Reader

Abstract

The invention relates to an electrochemical device and an electronic device. Specifically, the present application provides an electrochemical device including a positive electrode, a negative electrode including a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, in which the negative electrode current collector has high tensile strength, and the negative electrode active material layer has a specific weight, and an electrolyte solution. The electrochemical device has improved high-temperature storage expansion performance and cycle expansion performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese invention patent application with invention name “Electrochemical Device and Electronic Device”, application number 202011103536.8, and application date October 15, 2020. Technical Field

[0002] The present application relates to the field of energy storage, and in particular to an electrochemical device and an electronic device, in particular a lithium-ion battery. Background Art

[0003] With the development of technology and the increase in demand for mobile devices, people's demand for the battery life of electrochemical devices (such as lithium-ion batteries) is also increasing. While improving the battery life of lithium-ion batteries, higher requirements are placed on the performance of lithium-ion batteries, especially the high-temperature storage expansion performance and cycle expansion performance of lithium-ion batteries.

[0004] In view of the above, there is a real need to provide an electrochemical device and an electronic device with improved performance. Summary of the invention

[0005] The embodiments of the present application solve at least one problem existing in the related art to at least some extent by providing an electrochemical device and an electronic device with improved high temperature storage expansion performance and cycle expansion performance.

[0006] In one aspect of the present application, the present application provides an electrochemical device, comprising: a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, wherein: the tensile strength of the negative electrode current collector is FN / mm 2 , F is greater than 400, and the weight per unit area of ​​the negative electrode active material layer is W mg / cm 2 , W is in the range of 3 to 12.

[0007] According to an embodiment of the present application, the negative electrode current collector includes copper element.

[0008] According to an embodiment of the present application, the negative electrode current collector includes a first metal, the first metal includes at least one of silver or tin, and the content of the first metal is a%, based on the weight of the negative electrode current collector, and a is in the range of 0.01 to 0.5.

[0009] According to an embodiment of the present application, the negative electrode current collector further includes at least one rare earth element.

[0010] According to an embodiment of the present application, F and a satisfy: 4≤F×a≤200.

[0011] According to an embodiment of the present application, F and W satisfy: 100 / 3≤F / W≤200.

[0012] According to an embodiment of the present application, the density of the negative electrode active material layer is Dg / cm 3 , D is in the range of 1.4 to 2.0, and F and D satisfy: 560≤F×D≤1200.

[0013] According to an embodiment of the present application, the negative electrode current collector has at least one of the following characteristics:

[0014] 1) The average surface roughness is 0.05μm to 1.5μm;

[0015] 2) 0.2% endurance is 30N / mm 2 above;

[0016] 3) The thickness is 1 μm to 100 μm.

[0017] According to an embodiment of the present application, the negative electrode active material layer has at least one of the following characteristics:

[0018] a) the reflectivity Ra at a wavelength of 550nm is 7% to 15%;

[0019] b) The porosity Pa is 20% to 40%.

[0020] According to an embodiment of the present application, the electrolyte includes at least one of the following compounds:

[0021] i. Propionate;

[0022] ii. Compounds having a cyano group;

[0023] iii. lithium difluorophosphate; or

[0024] iv. Compounds of formula 1:

[0025]

[0026] in:

[0027] W is

[0028] L is each independently a single bond or a methylene group, and two Ls in the same ring structure are not simultaneously single bonds;

[0029] m is 1, 2, 3 or 4;

[0030] n is 0, 1 or 2.

[0031] According to an embodiment of the present application, the compound of formula 1 includes at least one of the following compounds:

[0032]

[0033]

[0034] According to an embodiment of the present application, the content of the compound having a cyano group is b%, based on the weight of the electrolyte, and b is in the range of 0.01 to 10.

[0035] According to an embodiment of the present application, a and b satisfy: 1≤b / a≤300.

[0036] According to an embodiment of the present application, W and b satisfy: 0.5≤W / b≤24.

[0037] In another aspect of the present application, the present application provides an electronic device, which includes the electrochemical device according to the present application.

[0038] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. DETAILED DESCRIPTION

[0039] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0040] Unless expressly stated otherwise, the following terms used herein have the meanings indicated below.

[0041] In the detailed description and claims, a list of items connected by the term "at least one of" may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements. The term "at least one of" has the same meaning as the term "at least one of."

[0042] As used herein, the term "alkyl" is expected to be a straight chain saturated hydrocarbon structure with 1 to 20 carbon atoms. "Alkyl" is also expected to be a branched or cyclic hydrocarbon structure with 3 to 20 carbon atoms. When specifying an alkyl with a specific carbon number, it is expected to cover all geometric isomers with that carbon number; therefore, for example, "butyl" means including n-butyl, sec-butyl, isobutyl, tert-butyl and cyclobutyl; "propyl" includes n-propyl, isopropyl and cyclopropyl. Alkyl examples include, but are not limited to methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, methylcyclopentyl, ethylcyclopentyl, n-hexyl, isohexyl, cyclohexyl, n-heptyl, octyl, cyclopropyl, cyclobutyl, norbornyl, etc.

[0043] As used herein, the term "halo" refers to that hydrogen atoms in a group are partially or fully substituted by halogen atoms (eg, fluorine, chlorine, bromine or iodine).

[0044] With the development of technology and the increase in demand for use, people's demand for the battery life of electrochemical devices (such as lithium-ion batteries) is also increasing. Long battery life puts higher requirements on the performance of lithium-ion batteries, especially the high-temperature storage expansion performance and cycle expansion performance of lithium-ion batteries.

[0045] In order to solve the above problems, the present application uses a negative electrode current collector with high tensile strength and a negative electrode active material layer with a specific weight, which can prevent the negative electrode from breaking under high temperature conditions, enable the electrochemical device to fully utilize its capacity, and significantly improve the high temperature storage expansion performance and cycle expansion performance of the electrochemical device.

[0046] In one embodiment, the present application provides an electrochemical device comprising a positive electrode, a negative electrode and an electrolyte as described below.

[0047] I. Negative electrode

[0048] The negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on one or both surfaces of the negative electrode current collector.

[0049] 1. Negative electrode current collector

[0050] As used herein, the term "tensile strength" refers to the ratio of the maximum tensile force required for a specimen to break to the cross-sectional area of ​​the specimen.

[0051] One feature of the electrochemical device of the present application is that the tensile strength of the negative electrode current collector is FN / mm 2, F is 400 or more. In some embodiments, F is 450 or more. In some embodiments, F is 500 or more. In some embodiments, F is 550 or more. In some embodiments, F is 600 or more. In some embodiments, F is 650 or more. In some embodiments, F is 700 or more. In some embodiments, F is 800 or more. In some embodiments, F is 900 or more. In some embodiments, F is 1000 or more.

[0052] The high tensile strength of the negative electrode current collector can be achieved by doping specific elements in the negative electrode current collector. Using a negative electrode current collector with high tensile strength can inhibit the cracking of the negative electrode current collector caused by the expansion / contraction of the negative electrode active material layer during the charge / discharge of the electrochemical device, thereby significantly improving the high temperature storage expansion performance and cycle expansion performance of the electrochemical device.

[0053] The tensile strength of the negative electrode current collector can be measured using the same device and method as that for measuring elongation (refer to the test method of GB-228-87).

[0054] In some embodiments, the negative electrode current collector may include, but is not limited to, metal foil, metal cylinder, metal strip, metal plate, metal film, metal mesh, stamped metal, foamed metal, etc. In some embodiments, the negative electrode current collector is metal foil. In some embodiments, the metal foil is meshed.

[0055] In some embodiments, the negative electrode current collector includes copper.

[0056] In some embodiments, the negative electrode current collector is a copper foil. As used herein, the term "copper foil" includes copper alloy foil.

[0057] In some embodiments, the negative electrode current collector includes at least one of tough pitch copper or oxygen-free copper. As used herein, the term "tough pitch copper" includes copper alloy foils based on tough pitch copper, and the term "oxygen-free copper" includes copper alloy foils based on oxygen-free copper.

[0058] In some embodiments, the tough copper complies with the JIS-H3100-C1100 standard. In some embodiments, the oxygen-free copper complies with the JIS-H3100-C1020 standard. The tough copper or oxygen-free copper that complies with the above standards has a composition close to pure copper, has good electrical conductivity, and is particularly suitable for use as a negative electrode current collector.

[0059] In some embodiments, the oxygen content of the tough pitch copper (based on copper) is 0.01% to 0.02%. In some embodiments, the oxygen content of the oxygen-free copper (based on copper) is less than 0.001%.

[0060] In some embodiments, the negative electrode current collector comprises a first metal, the first metal comprises at least one of silver or tin, and the content of the first metal is a%, based on the weight of the negative electrode current collector, and a is in the range of 0.01 to 0.5. In some embodiments, a is in the range of 0.05 to 0.4. In some embodiments, a is in the range of 0.1 to 0.3. In some embodiments, a is 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, or in the range consisting of any two of the above values. When the content of the first metal in the negative electrode current collector is in the range of 0.01% to 0.5%, it helps to inhibit the oxidation of the surface of the negative electrode current collector, so that the negative electrode current collector has good electrical conductivity, and the negative electrode current collector can be recrystallized during the drying step after coating the negative electrode active material layer in the preparation process of the negative electrode, further improving the high temperature storage expansion performance and cycle expansion performance of the electrochemical device.

[0061] In some embodiments, the negative electrode current collector further comprises at least one rare earth element.

[0062] In some embodiments, the rare earth element includes at least one of indium, yttrium, scandium, titanium, or vanadium.

[0063] In some embodiments, the copper foil contains impurities, and the impurities include at least one of P, Fe, Zr, Mg, S, Ge or Ti. In some embodiments, based on the weight of the copper foil, the content of the impurities is 20 ppm or less. When the impurity content in the copper foil is within the above range, the copper foil is not prone to bending deformation, thereby reducing the crystal orientation rotation and avoiding the generation of shear bands, which helps to improve the fracture resistance of the negative electrode collector.

[0064] In some embodiments, the tensile strength of the negative electrode current collector is FN / mm 2 The content a% of the first metal in the negative electrode current collector satisfies: 4≤F×a≤200. In some embodiments, 5≤F×a≤150. In some embodiments, 10≤F×a≤100. In some embodiments, 20≤F×a≤50. In some embodiments, F×a is 4, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200 or within the range of any two of the above values. When the tensile strength FN / mm 2 When the above relationship is satisfied with the content a% of the first metal in the negative electrode current collector, the high-temperature storage expansion performance and cycle expansion performance of the electrochemical device can be further improved.

[0065] In some embodiments, the negative electrode current collector has at least one of the following features (1)-(3):

[0066] (1) Average surface roughness

[0067] In some embodiments, the average surface roughness of the negative electrode current collector is 0.05 μm to 1.5 μm. In some embodiments, the average surface roughness of the negative electrode current collector is 0.1 μm to 1.3 μm. In some embodiments, the average surface roughness of the negative electrode current collector is 0.15 μm to 1.0 μm. In some embodiments, the average surface roughness of the negative electrode current collector is 0.2 μm to 0.8 μm. In some embodiments, the average surface roughness of the negative electrode current collector is 0.3 μm to 0.5 μm. In some embodiments, the average surface roughness of the negative electrode current collector is 0.05 μm, 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.3 μm, 1.5 μm, or within a range consisting of any two of the above values. When the average surface roughness of the negative electrode collector is within the above range, the interface area between the negative electrode collector and the negative electrode active material layer increases and the close adhesion between the negative electrode collector and the negative electrode active material improves, which helps to improve the high temperature storage expansion performance and cycle expansion performance of the electrochemical device.

[0068] The average surface roughness of the negative electrode current collector can be measured by the method described in ISO1302:2002.

[0069] (2) 0.2% Stamina

[0070] As used herein, the term "0.2% proof strength" refers to the load required to produce 0.2% plastic deformation (i.e., permanent deformation) of a specimen. In other words, after the load is applied to produce 0.2% plastic deformation of the specimen, the specimen still maintains 0.2% plastic deformation even if the load is removed.

[0071] In some embodiments, the 0.2% endurance of the negative electrode current collector is 30 N / mm 2 In some embodiments, the 0.2% endurance of the negative electrode current collector is 50 N / mm 2 In some embodiments, the 0.2% endurance of the negative electrode current collector is 100 N / mm 2 In some embodiments, the 0.2% endurance of the negative electrode current collector is 150 N / mm 2 In some embodiments, the 0.2% endurance of the negative electrode current collector is 200 N / mm 2 In some embodiments, the 0.2% endurance of the negative electrode current collector is 300 N / mm 2When the 0.2% resistance of the negative electrode current collector is within the above range, cracking of the negative electrode current collector caused by expansion or contraction of the negative electrode active material layer during charge / discharge of the electrochemical device can be suppressed, thereby improving high temperature storage expansion performance and cycle expansion performance.

[0072] The 0.2% resistance of the negative electrode current collector can be measured using the same device and method as that for measuring the elongation (refer to the test method of GB-228-87).

[0073] (3) Thickness

[0074] In some embodiments, the thickness of the negative electrode current collector is 1 μm to 100 μm. In some embodiments, the thickness of the negative electrode current collector is 3 μm to 80 μm. In some embodiments, the thickness of the negative electrode current collector is 5 μm to 50 μm. In some embodiments, the thickness of the negative electrode current collector is 10 μm to 30 μm. In some embodiments, the thickness of the negative electrode current collector is 15 μm to 20 μm. In some embodiments, the thickness of the negative electrode current collector is 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm or in the range consisting of any two of the above values. When the thickness of the negative electrode current collector is within the above range, the negative electrode current collector has high strength and is easy to apply, and the shape of the negative electrode is less likely to be deformed such as curling.

[0075] 2. Negative electrode active material layer

[0076] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer may be one or more layers, and each layer of the multiple layers of negative electrode active material may contain the same or different negative electrode active materials. The negative electrode active material is any material that can reversibly embed and deintercalate metal ions such as lithium ions. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.

[0077] Another feature of the electrochemical device of the present application is that the weight per unit area of ​​the negative electrode active material layer is W mg / cm 2, W is in the range of 3 to 12. In some embodiments, W is in the range of 5 to 10. In some embodiments, W is in the range of 6 to 8. In some embodiments, W is 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or in the range consisting of any two of the above values. When the weight per unit area of ​​the negative electrode active material layer is in the above range, it helps to improve the permeability of the electrolyte to the interface between the negative electrode current collector and the negative electrode active material layer, improve the electron transport in the electrochemical device, and at the same time reduce the impact on the active material layer during processing, so that the interface between the negative electrode current collector and the negative electrode active material layer is maintained in good condition, and the relative displacement between the negative electrode active materials is reduced, thereby improving the high temperature storage expansion performance and cycle expansion performance of the electrochemical device.

[0078] In some embodiments, the tensile strength of the negative electrode current collector is FN / mm 2 The weight per unit area of ​​the negative electrode active material layer is Wmg / cm 2 Satisfies: 100 / 3≤F / W≤200. In some embodiments, 40≤F / W≤150. In some embodiments, 50≤F / W≤100. In some embodiments, 60≤F / W≤80. In some embodiments, F / W is 100 / 3, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200 or within a range consisting of any two of the above values. When the tensile strength FN / mm 2 The weight per unit area of ​​the negative electrode active material layer is Wmg / cm 2 When the above relationship is satisfied, the high-temperature storage expansion performance and cycle expansion performance of the electrochemical device can be further improved.

[0079] The weight per unit area of ​​the negative electrode active material layer in this application is the mass (mg) of the negative electrode active material layer relative to the area (cm 2 ) ratio. The mass and area of ​​the negative electrode active material layer are obtained by the following method: cut a test piece of appropriate size from the negative electrode, measure its area as S1 and mass W0, then peel the negative electrode current collector from the negative electrode, measure the mass W1 of the negative electrode current collector, and calculate the mass of the negative electrode active material layer from (W0-W1), and the weight per unit area = (W0-W1) / S1. If the selected negative electrode is a double-sided active material layer, the weight per unit area = (W0-W1) / S1 / 2.

[0080] Examples of a method for peeling the negative electrode active material layer include immersing the negative electrode active material layer in a solvent that can dissolve or swell the negative electrode active material layer, and wiping the active material layer with a cloth or the like.

[0081] The weight per unit area of ​​the negative electrode active material layer can be adjusted by a known method. For example, when the negative electrode active material layer is formed by coating, it can be adjusted by changing the solid content concentration of the coating liquid used to form the negative electrode active material layer, the number of coatings, the gap between the coating liquid inlet of the coating machine, etc. The weight per unit area of ​​the negative electrode active material layer can be increased by increasing the solid content concentration, increasing the number of coatings, or increasing the gap. The weight per unit area of ​​the negative electrode active material layer can be reduced by reducing the solid content concentration, reducing the number of coatings, or reducing the gap.

[0082] In some embodiments, the density of the negative electrode active material layer is Dg / cm 3 , D is in the range of 1.4 to 2.0. In some embodiments, D is in the range of 1.5 to 1.8. In some embodiments, D is 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or in the range consisting of any two of the above values. When the density of the negative electrode active material layer is within the above range, the negative electrode active material is not easily destroyed, and a low initial irreversible capacity can be maintained, so that the negative electrode active material maintains high conductivity, and at the same time, the permeability of the electrolyte to the interface between the negative electrode current collector and the negative electrode active material layer can be improved, thereby helping to improve the high temperature storage expansion performance and cycle expansion performance of the electrochemical device.

[0083] In some embodiments, the tensile strength of the negative electrode current collector is FN / mm 2 The density of the negative electrode active material layer is Dg / cm 3 Satisfies: 560≤F×D≤1200. In some embodiments, 600≤F×D≤1000. In some embodiments, 700≤F×D≤800. In some embodiments, F×D is 560, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050, 1100, 1150, 1200 or within the range of any two of the above values. When the tensile strength of the negative electrode current collector is FN / mm 2 The density of the negative electrode active material layer is Dg / cm 3 When the above relationship is satisfied, the high-temperature storage expansion performance and cycle expansion performance of the electrochemical device can be further improved.

[0084] In some embodiments, the negative electrode active material layer has at least one of the following features (a) and (b):

[0085] (a) Reflectivity

[0086] The reflectivity of the negative electrode active material layer can reflect the smoothness of the surface of the negative electrode active material layer and the surface compression state of the negative electrode active material. The reflectivity of the negative electrode active material layer can be controlled by the type of negative electrode active material, the molding conditions of the negative electrode active material layer and the post-processing process after molding, and can also be controlled by the rolling pressure, the number of rolling times, the heating conditions during rolling, the rolling plate used during rolling, and the material and surface shape of the rolling roller.

[0087] In some embodiments, the reflectivity Ra of the negative electrode active material layer at a wavelength of 550nm is 7% to 15%. In some embodiments, the reflectivity Ra of the negative electrode active material layer at a wavelength of 550nm is 8% to 14.8%. In some embodiments, the reflectivity Ra of the negative electrode active material layer at a wavelength of 550nm is 10% to 12%. In some embodiments, the reflectivity Ra of the negative electrode active material layer at a wavelength of 550nm is 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or in the range consisting of any two of the above values. When the reflectivity of the negative electrode active material layer is within the above range, the side reactions on the surface of the negative electrode active material layer can be suppressed, and the permeability of the electrolyte from the surface of the negative electrode active material layer to the inside of the negative electrode active material layer can be improved, thereby improving the fast charging characteristics of the electrochemical device.

[0088] The reflectance of the negative electrode active material layer can be measured using a commercially available spectrocolorimeter (for example, SPECTRO PHOTOMETER CM-5 manufactured by KONICAMINOLTA).

[0089] (b) Porosity

[0090] In some embodiments, the porosity Pa of the negative electrode active material layer is 20% to 40%. In some embodiments, the porosity Pa of the negative electrode active material layer is 26.5% to 31.3%. In some embodiments, the porosity Pa of the negative electrode active material layer is 26% to 31%. In some embodiments, the porosity Pa of the negative electrode active material layer is 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40% or in the range consisting of any two of the above values.

[0091] The porosity of the negative electrode active material layer can be determined by the following method: Use a punching machine to punch the negative electrode into 13mm small discs, and use a micrometer to measure the thickness of the small discs. Put a certain number of small discs into the sample chamber of the AccuPyc 1340 instrument, purge the sample with helium 30 times, and then introduce helium according to the procedure. By testing the pressure in the sample chamber, the true volume in the sample chamber is calculated using Bohr's law PV=nRT. After the test is completed, count the number of small discs and calculate the apparent volume of the sample. The porosity of the sample is calculated by the following formula:

[0092] Porosity = 1 - true volume / apparent volume.

[0093] Negative active material

[0094] In some embodiments, the negative electrode active material includes, but is not limited to, graphite, hard carbon, soft carbon, MCMB and other carbon materials, silicon, SiO x Silicon compounds such as silicon oxide represented by (0<x<2), metallic lithium, metals forming alloys with lithium and alloys thereof, amorphous compounds mainly composed of oxides such as tin dioxide, and lithium titanate (Li4Ti5O 12 ).

[0095] In some embodiments, the negative electrode active material comprises a carbon material. In some embodiments, the negative electrode active material comprises a carbon material having a graphite structure. In some embodiments, the negative electrode active material is at least one of artificial graphite or natural graphite.

[0096] In some embodiments, the negative electrode active material includes different components, wherein the carbon material having a graphite structure is predominant. In some embodiments, the content of the carbon material having a graphite structure is 70.0% or more based on the weight of the negative electrode active material layer. In some embodiments, the content of the carbon material having a graphite structure is 90.0% or more based on the weight of the negative electrode active material layer. The content of the carbon material having a graphite structure is 95.0% or more based on the weight of the negative electrode active material layer.

[0097] In some embodiments, metals that form alloys with metallic lithium include, but are not limited to, aluminum, silicon, tin, germanium, and the like.

[0098] In some embodiments, the negative electrode active material is a metal or semi-metal that forms an alloy with lithium, represented by silicon, and their alloys, which have high charge and discharge capacity.

[0099] In some embodiments, the negative electrode active material includes a mixture of a metal or semi-metal that forms an alloy with lithium, represented by silicon, and an alloy thereof, and a carbon material having a graphite structure.

[0100] Adhesives

[0101] In some embodiments, the negative electrode active material layer further includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material layer and the negative electrode current collector. The type of the negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the electrolyte or electrode manufacturing.

[0102] Examples of negative electrode binders include, but are not limited to, resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as SBR (styrene butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile butadiene rubber), and styrene-propylene rubber; styrene-butadiene-styrene block copolymers or their hydrogenated products; thermoplastic elastomer polymers such as EPDM (ethylene-propylene-diene terpolymer), styrene-ethylene-butadiene-styrene copolymers, styrene-isobutylene-styrene block copolymers or their hydrogenated products; soft resin polymers such as syndiotactic 1,2 polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc. The above negative electrode binders may be used alone or in any combination.

[0103] In some embodiments, the content of the negative electrode binder is greater than 0.1%, greater than 0.5%, or greater than 0.6%, based on the weight of the negative electrode active material layer. In some embodiments, the content of the negative electrode binder is less than 10%, less than 8%, less than 5%, or less than 4%, based on the weight of the negative electrode active material layer. In some embodiments, the content of the negative electrode binder is within the range consisting of any two of the above values. When the content of the negative electrode binder is within the above range, the capacity of the electrochemical device and the strength of the negative electrode can be fully ensured.

[0104] In the case where the negative electrode active material layer contains a rubber-like polymer (e.g., SBR), in some embodiments, the content of the negative electrode binder is greater than 0.1%, greater than 0.5%, or greater than 0.6% based on the weight of the negative electrode active material layer. In some embodiments, the content of the negative electrode binder is less than 5%, less than 3%, or less than 2% based on the weight of the negative electrode active material layer. In some embodiments, the content of the negative electrode binder is within the range formed by any two of the above values ​​based on the weight of the negative electrode active material layer.

[0105] In the case where the negative electrode active material layer contains a fluorine-based polymer (e.g., polyvinylidene fluoride), in some embodiments, based on the weight of the negative electrode active material layer, the content of the negative electrode binder is greater than 1%, greater than 2%, or greater than 3%. In some embodiments, based on the weight of the negative electrode active material layer, the content of the negative electrode binder is less than 10%, less than 8%, or less than 5%. Based on the weight of the negative electrode active material layer, the content of the negative electrode binder is within the range consisting of any two of the above values.

[0106] Thickener

[0107] Thickeners are generally used to adjust the viscosity of negative electrode slurry. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.

[0108] In some embodiments, the content of the thickener is greater than 0.1%, greater than 0.5%, or greater than 0.6% based on the weight of the negative electrode active material layer. In some embodiments, the content of the thickener is less than 5%, less than 3%, or less than 2% based on the weight of the negative electrode active material layer. When the content of the thickener is within the above range, the capacity reduction and the increase of the resistance of the electrochemical device can be suppressed, and the negative electrode slurry can be ensured to have good coating properties.

[0109] Solvents

[0110] The type of solvent used to form the negative electrode slurry is not particularly limited, as long as it is a solvent that can dissolve or disperse the negative electrode active material, the negative electrode binder, and the thickener and conductive material used as needed. In some embodiments, the solvent used to form the negative electrode slurry can use any of an aqueous solvent and an organic solvent. Examples of aqueous solvents may include, but are not limited to, water, alcohol, and the like. Examples of organic solvents may include, but are not limited to, N-methylpyrrolidone (NMP), dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethyltriamine, N, N-dimethylaminopropylamine, tetrahydrofuran (THF), toluene, acetone, diethyl ether, hexamethylphosphoramide, dimethyl sulfoxide, benzene, xylene, quinoline, pyridine, methylnaphthalene, hexane, and the like. The above solvents may be used alone or in any combination.

[0111] Preparation of negative electrode

[0112] The negative electrode in the electrochemical device of the present application can be prepared by any known method. For example, a binder, a solvent, a thickener, a conductive material, a filler, etc. are added to the negative electrode active material to prepare a slurry, and the slurry is applied to the negative electrode current collector, and the electrode is formed by pressing after drying. The negative electrode active material can also be roll-formed into a sheet electrode, or compressed into a particle electrode.

[0113] II. Electrolyte

[0114] The electrolyte used in the electrochemical device of the present application includes an electrolyte and a solvent that dissolves the electrolyte. In some embodiments, the electrolyte used in the electrochemical device of the present application further includes an additive.

[0115] According to some embodiments of the present application, the electrolyte further includes at least one of the following compounds:

[0116] i. Propionate;

[0117] ii. Compounds having a cyano group;

[0118] iii. lithium difluorophosphate; or

[0119] iv. Compounds of formula 1:

[0120]

[0121] in:

[0122] W is

[0123] L is each independently a single bond or a methylene group, and two Ls in the same ring structure are not simultaneously single bonds;

[0124] m is 1, 2, 3 or 4;

[0125] n is 0, 1 or 2.

[0126] (i) Propionate

[0127] In some embodiments, the propionate ester comprises a compound of Formula 2:

[0128]

[0129] in:

[0130] R 1 is selected from ethyl or haloethyl, and

[0131] R 2 Selected from C1-C6 alkyl or C1-C6 haloalkyl.

[0132] In certain embodiments, the propionic ester includes, but is not limited to, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, pentyl propionate, methyl halogenated propionate, ethyl halogenated propionate, propyl halogenated propionate, butyl halogenated propionate and pentyl halogenated propionate. In certain embodiments, the propionic ester is selected from at least one of methyl propionate, ethyl propionate, propyl propionate, butyl propionate and pentyl propionate. In certain embodiments, the halogen group in the methyl halogenated propionate, ethyl halogenated propionate, propyl halogenated propionate, butyl halogenated propionate and pentyl halogenated propionate is selected from one or more of fluorine group (-F), chlorine group (-Cl), bromine group (-Br) and iodine group (-I). In certain embodiments, the halogen group is a fluorine group (-F), which can achieve a more excellent effect.

[0133] In some embodiments, the content of the propionate ester is 10% to 60% based on the weight of the electrolyte. In some embodiments, the content of the propionate ester is 20% to 50% based on the weight of the electrolyte. In some embodiments, the content of the propionate ester is 30% to 40% based on the weight of the electrolyte. In some embodiments, the content of the propionate ester is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or in a range consisting of any two of the above values ​​based on the weight of the electrolyte.

[0134] (ii) Compounds having a cyano group

[0135] In some embodiments, the compound having a cyano group includes, but is not limited to, one or more of the following: succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, ethylene glycol bis(propionitrile) ether, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, diethylene glycol di(2-cyanoethyl)ether, triethylene glycol di(2-cyanoethyl)ether, tetraethylene glycol di(2-cyanoethyl)ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl)ether, 1,4-dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexatriconitrile, 1,2,6-hexatriconitrile , 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane and 1,2,5-tris(cyanoethoxy)pentane.

[0136] The above compounds having a cyano group can be used alone or in any combination. If the electrolyte contains two or more compounds having a cyano group, the content of the compound having a cyano group refers to the total content of the two or more compounds having a cyano group.

[0137] In some embodiments, the content of the compound having a cyano group is b%, based on the weight of the electrolyte, and b is in the range of 0.01 to 10. In some embodiments, b is in the range of 0.1 to 8. In some embodiments, b is in the range of 0.5 to 5. In some embodiments, b is in the range of 1 to 3. In some embodiments, b is 0.01, 0.05, 0.1, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or in the range consisting of any two of the above values. When the content of the compound having a cyano group in the electrolyte is within the above range, it helps to further improve the high temperature storage expansion performance and cycle expansion performance of the electrochemical device.

[0138] In some embodiments, the content of the compound having a cyano group in the electrolyte is b% and the content of the first metal in the negative electrode current collector is a% and satisfies: 1≤b / a≤300. In some embodiments, 5≤b / a≤250. In some embodiments, 10≤b / a≤200. In some embodiments, 50≤b / a≤150. In some embodiments, 80≤b / a≤100. In some embodiments, b / a is 1, 5, 10, 20, 50, 80, 100, 120, 150, 180, 200, 220, 250, 280, 300 or within the range consisting of any two of the above values. When the content of the compound having a cyano group in the electrolyte is b% and the content of the first metal in the negative electrode current collector is a% and satisfies the above relationship, it helps to further improve the high temperature storage expansion performance and cycle expansion performance of the electrochemical device.

[0139] In some embodiments, the content of the compound having a cyano group in the electrolyte is b% and the weight per unit area of ​​the negative electrode active material layer is W mg / cm 2 Satisfies: 0.5≤W / b≤24. In some embodiments, 1≤W / b≤20. In some embodiments, 5≤W / b≤15. In some embodiments, 8≤W / b≤10. In some embodiments, W / b is 0.5, 1, 2, 5, 8, 10, 12, 15, 18, 20, 22, 24 or in a range consisting of any two of the above values. When the content of the compound having a cyano group in the electrolyte is b% and the weight per unit area of ​​the negative electrode active material layer is Wmg / cm 2 When the above relationship is satisfied, it helps to further improve the high-temperature storage expansion performance and cycle expansion performance of the electrochemical device.

[0140] (iii) Lithium difluorophosphate (LiPO2F2)

[0141] In some embodiments, the content of lithium difluorophosphate is 0.01% to 1.5% based on the weight of the electrolyte. In some embodiments, the content of lithium difluorophosphate is 0.05% to 1.2% based on the weight of the electrolyte. In some embodiments, the content of lithium difluorophosphate is 0.1% to 1.0% based on the weight of the electrolyte. In some embodiments, the content of lithium difluorophosphate is 0.5% to 0.8% based on the weight of the electrolyte. In some embodiments, the content of lithium difluorophosphate is 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.8%, 1%, 1.5% or in the range of any two of the above values ​​based on the weight of the electrolyte.

[0142] (iv) Compounds of formula 1

[0143] In some embodiments, the compound of Formula 1 includes at least one of the following compounds:

[0144]

[0145] In some embodiments, the content of the compound of formula 1 is 0.01% to 5% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is 0.05% to 3% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is 0.1% to 2% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is 0.5% to 1% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 1 is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or in the range of any two of the above values ​​based on the weight of the electrolyte.

[0146] Solvents

[0147] In some embodiments, the electrolyte further comprises any non-aqueous solvent known in the prior art that can be used as a solvent for the electrolyte.

[0148] In some embodiments, the non-aqueous solvent includes, but is not limited to, one or more of the following: cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, cyclic ethers, chain ethers, phosphorus-containing organic solvents, sulfur-containing organic solvents, and aromatic fluorine-containing solvents.

[0149] In some embodiments, examples of the cyclic carbonate may include, but are not limited to, one or more of the following: ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate. In some embodiments, the cyclic carbonate has 3-6 carbon atoms.

[0150] In some embodiments, examples of the linear carbonates may include, but are not limited to, one or more of the following: dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate (DEC), methyl n-propyl carbonate, ethyl n-propyl carbonate, di-n-propyl carbonate, etc. Examples of fluorine-substituted linear carbonates may include, but are not limited to, one or more of the following: bis(fluoromethyl) carbonate, bis(difluoromethyl) carbonate, bis(trifluoromethyl) carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2-fluoroethyl methyl carbonate, 2,2-difluoroethyl methyl carbonate, and 2,2,2-trifluoroethyl methyl carbonate, etc.

[0151] In some embodiments, examples of the cyclic carboxylic acid ester may include, but are not limited to, one or more of the following: one or more of γ-butyrolactone and γ-valerolactone. In some embodiments, part of the hydrogen atoms of the cyclic carboxylic acid ester may be substituted with fluorine.

[0152] In some embodiments, examples of the chain carboxylic acid esters may include, but are not limited to, one or more of the following: methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate and ethyl pivalate, etc. In some embodiments, some hydrogen atoms of the chain carboxylic acid ester may be substituted by fluorine. In some embodiments, examples of fluorine-substituted chain carboxylic acid esters may include, but are not limited to, methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate and 2,2,2-trifluoroethyl trifluoroacetate, etc.

[0153] In some embodiments, examples of the cyclic ether may include, but are not limited to, one or more of the following: tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl1,3-dioxolane, 4-methyl1,3-dioxolane, 1,3-dioxane, 1,4-dioxane and dimethoxypropane.

[0154] In some embodiments, examples of the chain ether may include, but are not limited to, one or more of the following: dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane and 1,2-ethoxymethoxyethane, etc.

[0155] In some embodiments, examples of the phosphorus-containing organic solvent may include, but are not limited to, one or more of the following: trimethyl phosphate, triethyl phosphate, dimethyl ethyl phosphate, diethyl methyl phosphate, ethylidene methyl phosphate, ethylidene ethyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphate, and tris(2,2,3,3,3-pentafluoropropyl) phosphate, etc.

[0156] In some embodiments, examples of the sulfur-containing organic solvent may include, but are not limited to, one or more of the following: sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethyl sulfone, diethyl sulfone, ethyl methyl sulfone, methyl propyl sulfone, dimethyl sulfoxide, methyl methanesulfonate, ethyl methanesulfonate, methyl ethanesulfonate, ethyl ethanesulfonate, dimethyl sulfate, diethyl sulfate, and dibutyl sulfate. In some embodiments, some hydrogen atoms of the sulfur-containing organic solvent may be substituted by fluorine.

[0157] In some embodiments, the aromatic fluorine-containing solvent includes, but is not limited to, one or more of the following: fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, and trifluoromethylbenzene.

[0158] In some embodiments, the solvent used in the electrolyte of the present application includes cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes an organic solvent selected from the group consisting of the following substances: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, ethyl acetate, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, and combinations thereof.

[0159] additive

[0160] In some embodiments, examples of the additive may include, but are not limited to, one or more of the following: fluorocarbonate, ethylene carbonate containing a carbon-carbon double bond, a compound containing a sulfur-oxygen double bond, and an acid anhydride.

[0161] In some embodiments, the additive is present in an amount of 0.01% to 15%, 0.1% to 10%, or 1% to 5%, based on the weight of the electrolyte.

[0162] According to an embodiment of the present application, based on the weight of the electrolyte, the content of the propionate is 1.5 to 30 times, 1.5 to 20 times, 2 to 20 times, or 5 to 20 times that of the additive.

[0163] In some embodiments, the additive comprises one or more fluorocarbonates. During the charging / discharging of the lithium-ion battery, the fluorocarbonates can work together with the propionate to form a stable protective film on the surface of the negative electrode, thereby inhibiting the decomposition reaction of the electrolyte.

[0164] In some embodiments, the fluorinated carbonate has the formula C=O(OR x )(OR y ), where R x and R y Each is selected from an alkyl or halogenated alkyl group having 1 to 6 carbon atoms, wherein R x and R y At least one of them is selected from a fluoroalkyl group having 1 to 6 carbon atoms, and R x and R y Optionally together with the atoms to which it is attached, it forms a 5- to 7-membered ring.

[0165] In some embodiments, examples of the fluorinated carbonates may include, but are not limited to, one or more of the following: fluoroethylene carbonate, cis-4,4-difluoroethylene carbonate, trans-4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate, and ethyl trifluoroethyl carbonate, etc.

[0166] In some embodiments, the additive comprises one or more ethylene carbonates containing carbon-carbon double bonds. Examples of the ethylene carbonates containing carbon-carbon double bonds may include, but are not limited to, one or more of the following: vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, fluoro vinylene carbonate, trifluoromethyl vinylene carbonate; vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1-ethyl-2-vinyl ethylene carbonate, 1-n-propyl-2-vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1,1-divinyl ethylene carbonate, 1,2-divinyl ethylene carbonate, 1,1-dimethyl-2-methylene ethylene carbonate and 1,1-diethyl-2-methylene ethylene carbonate, etc. In some embodiments, the ethylene carbonate containing carbon-carbon double bonds includes vinylene carbonate, which is easy to obtain and can achieve more excellent effects.

[0167] In some embodiments, the additive is a combination of fluorocarbonic acid ester and ethylene carbonate containing carbon-carbon double bonds. In some embodiments, the additive is a combination of fluorocarbonic acid ester and a compound containing sulfur-oxygen double bonds. In some embodiments, the additive is a combination of fluorocarbonic acid ester and a compound with 2-4 cyano groups. In some embodiments, the additive is a combination of fluorocarbonic acid ester and cyclic carboxylic acid ester. In some embodiments, the additive is a combination of fluorocarbonic acid ester and cyclic phosphoric acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and carboxylic acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and sulfonic acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and carboxylic acid sulfonic acid anhydride.

[0168] Electrolytes

[0169] The electrolyte is not particularly limited, and any substance known as an electrolyte can be used arbitrarily. In the case of a lithium secondary battery, a lithium salt is generally used. Examples of the electrolyte may include, but are not limited to, inorganic lithium salts such as LiPF6, LiBF4, LiClO4, LiAlF4, LiSbF6, and LiWF7; lithium tungstates such as LiWOF5; lithium carboxylates such as HCO2Li, CH3CO2Li, CH2FCO2Li, CHF2CO2Li, CF3CO2Li, CF3CH2CO2Li, CF3CF2CO2Li, CF3CF2CF2CO2Li, and CF3CF2CF2CF2CO2Li; lithium salts such as FSO3Li, CH3SO3Li 、CH2FSO3Li、CHF2SO3Li、CF3SO3Li、CF3CF2SO3Li、CF3CF2CF2SO3Li、CF3CF2CF2CF2SO3Li and other lithium sulfonate salts; LiN(FCO)2、LiN(FCO)(FSO2)、LiN(FSO2)2、LiN(FSO2)(CF3SO2)、LiN(CF3SO2)2、LiN(C2F5SO2)2、Cyclic 1,2-perfluoroethane bissulfonyl imide lithium、Cyclic 1,3-perfluoropropane bissulfonyl imide Lithium, LiN(CF3SO2)(C4F9SO2) and other imide lithium salts; LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3 and other methylated lithium salts; (malonate) borate lithium salts such as bis(malonate) borate and difluoro(malonate) borate lithium salts; (malonate) phosphate lithium salts such as tris(malonate) phosphate, difluorobis(malonate) phosphate, tetrafluoro(malonate) phosphate; and LiPF4(CF3)2, LiPF4(C2F5)2, Fluorine-containing organic lithium salts such as LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF3CF3, LiBF3C2F5, LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium oxalate borate salts such as lithium difluorooxalatoborate and lithium bis(oxalato)borate; lithium oxalate phosphate salts such as lithium tetrafluorooxalato phosphate, lithium difluorobis(oxalato) phosphate and lithium tris(oxalato) phosphate, etc.

[0170] In some embodiments, the electrolyte is selected from LiPF6, LiSbF6, FSO3Li, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonyl imide lithium, cyclic 1,3-perfluoropropane bissulfonyl imide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3, lithium difluorooxalatoborate, lithium bis(oxalate)borate or lithium difluorobis(oxalato)phosphate, which helps to improve the output power characteristics, high-rate charge and discharge characteristics, high-temperature storage characteristics and cycle characteristics of the electrochemical device.

[0171] The content of the electrolyte is not particularly limited as long as it does not impair the effect of the present application. In some embodiments, the total molar concentration of lithium in the electrolyte is greater than 0.3 mol / L, greater than 0.4 mol / L or greater than 0.5 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is less than 3 mol / L, less than 2.5 mol / L or less than 2.0 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is within the range formed by any two of the above values. When the electrolyte concentration is within the above range, there will not be too little lithium as a charged particle, and the viscosity can be kept within an appropriate range, thereby easily ensuring good conductivity.

[0172] When more than two electrolytes are used, the electrolyte includes at least one salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a salt selected from the group consisting of monofluorophosphate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a lithium salt. In some embodiments, based on the weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is greater than 0.01% or greater than 0.1%. In some embodiments, based on the weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is less than 20% or less than 10%. In some embodiments, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is within the range of any two of the above values.

[0173] In some embodiments, the electrolyte comprises one or more substances selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate and one or more salts other than this. As salts other than this, the lithium salts exemplified above can be cited, and in some embodiments, they are LiPF6, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonyl imide lithium, cyclic 1,3-perfluoropropane bissulfonyl imide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3. In some embodiments, the salt other than this is LiPF6.

[0174] In some embodiments, the content of the other salt is greater than 0.01% or greater than 0.1% based on the weight of the electrolyte. In some embodiments, the content of the other salt is less than 20%, less than 15%, or less than 10% based on the weight of the electrolyte. In some embodiments, the content of the other salt is within the range formed by any two of the above values. The other salt having the above content helps to balance the conductivity and viscosity of the electrolyte.

[0175] In addition to the above-mentioned solvents, additives and electrolyte salts, the electrolyte may contain additional additives such as negative electrode film formers, positive electrode protective agents, and anti-overcharge agents as needed. As additives, additives generally used in non-aqueous electrolyte secondary batteries may be used, examples of which may include, but are not limited to, vinylene carbonate, succinic anhydride, biphenyl, cyclohexylbenzene, 2,4-difluoroanisole, propane sultone, propene sultone, and the like. These additives may be used alone or in any combination. In addition, the content of these additives in the electrolyte is not particularly limited and can be appropriately set according to the type of the additive, etc. In some embodiments, the content of the additive is less than 5%, in the range of 0.01% to 5%, or in the range of 0.2% to 5%, based on the weight of the electrolyte.

[0176] III. Positive electrode

[0177] The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on one or both surfaces of the positive electrode current collector.

[0178] 1. Positive electrode active material layer

[0179] The positive electrode active material layer contains a positive electrode active material, and the positive electrode active material layer can be one layer or multiple layers. Each layer of the multiple layers of positive electrode active material can contain the same or different positive electrode active materials. The positive electrode active material is any material that can reversibly embed and de-embed metal ions such as lithium ions.

[0180] There is no particular limitation on the type of positive electrode active material, as long as it can electrochemically absorb and release metal ions (e.g., lithium ions). In some embodiments, the positive electrode active material is a material containing lithium and at least one transition metal. Examples of positive electrode active materials may include, but are not limited to, lithium transition metal composite oxides and lithium-containing transition metal phosphate compounds.

[0181] In some embodiments, the transition metal in the lithium transition metal composite oxide includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium transition metal composite oxide includes lithium cobalt composite oxides such as LiCoO2, lithium nickel composite oxides such as LiNiO2, lithium manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO4, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2 and the like, wherein a portion of the transition metal atoms serving as the main body of these lithium transition metal composite oxides are replaced by other elements such as Na, K, B, F, Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, Nb, Mo, Sn, W, etc. Examples of lithium transition metal composite oxides may include, but are not limited to, LiNi 0.5 Mn 0.5 O2、LiNi 0.85 Co 0.10 Al 0.05 O2、LiNi 0.33 Co 0.33 Mn 0.33 O2、LiNi 0.45 Co 0.10 Al 0.45 O2、LiMn 1.8 Al 0.2 O4 and LiMn 1.5 Ni 0.5 O4, etc. Examples of combinations of lithium transition metal composite oxides include, but are not limited to, combinations of LiCoO2 and LiMn2O4, wherein a portion of the Mn in LiMn2O4 can be replaced by a transition metal (e.g., LiNi 0.33 Co 0.33 Mn0.33 O2), part of the Co in LiCoO2 can be replaced by transition metals.

[0182] In some embodiments, the transition metal in the lithium-containing transition metal phosphate compound includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium-containing transition metal phosphate compound includes iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, and cobalt phosphates such as LiCoPO4, wherein a portion of the transition metal atoms as the main body of these lithium transition metal phosphate compounds are replaced by other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.

[0183] In some embodiments, the positive electrode active material includes lithium phosphate, which can improve the continuous charging characteristics of the electrochemical device. There is no limitation on the use of lithium phosphate. In some embodiments, the positive electrode active material and lithium phosphate are mixed. In some embodiments, the content of lithium phosphate is greater than 0.1%, greater than 0.3% or greater than 0.5% relative to the weight of the above-mentioned positive electrode active material and lithium phosphate. In some embodiments, the content of lithium phosphate is less than 10%, less than 8% or less than 5% relative to the weight of the above-mentioned positive electrode active material and lithium phosphate. In some embodiments, the content of lithium phosphate is within the range formed by any two of the above-mentioned values.

[0184] surface coating

[0185] A substance having a different composition from that of the positive electrode active material may be attached to the surface of the positive electrode active material. Examples of the surface-attached substance may include, but are not limited to, oxides such as aluminum oxide, silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.

[0186] These surface-attached substances can be attached to the surface of the positive electrode active material by the following methods: a method in which the surface-attached substance is dissolved or suspended in a solvent and then added to the positive electrode active material and dried; a method in which a surface-attached substance precursor is dissolved or suspended in a solvent, added to the positive electrode active material, and then reacted by heating or the like; and a method in which the surface-attached substance is added to the positive electrode active material precursor and then fired simultaneously, etc. In the case of carbon attachment, a method in which a carbon material (e.g., activated carbon, etc.) is mechanically attached can also be used.

[0187] In some embodiments, the content of the surface-attached substance is greater than 0.1 ppm, greater than 1 ppm, or greater than 10 ppm based on the weight of the positive electrode active material layer. In some embodiments, the content of the surface-attached substance is less than 20%, less than 10%, or less than 10% based on the weight of the positive electrode active material layer. In some embodiments, the content of the surface-attached substance is within the range of any two of the above values ​​based on the weight of the positive electrode active material layer.

[0188] By attaching substances to the surface of the positive electrode active material, the oxidation reaction of the electrolyte on the surface of the positive electrode active material can be suppressed, and the life of the electrochemical device can be improved. When the amount of surface-attached substances is too small, the effect cannot be fully demonstrated; when the amount of surface-attached substances is too large, it will hinder the entry and exit of lithium ions, and the resistance may sometimes increase.

[0189] In the present application, a positive electrode active material in which a substance having a composition different from that of the positive electrode active material is attached to the surface of the positive electrode active material is also referred to as a “positive electrode active material”.

[0190] shape

[0191] In some embodiments, the shape of the positive electrode active material particles includes, but is not limited to, block, polyhedron, sphere, ellipsoid, plate, needle and column, etc. In some embodiments, the positive electrode active material particles include primary particles, secondary particles or a combination thereof. In some embodiments, the primary particles can be agglomerated to form secondary particles.

[0192] Tap density

[0193] In some embodiments, the tap density of the positive electrode active material is greater than 0.5 g / cm 3 , greater than 0.8g / cm 3 Or greater than 1.0g / cm 3 . When the tap density of the positive electrode active material is within the above range, the amount of dispersion medium and the required amount of conductive material and positive electrode binder required for the formation of the positive electrode active material layer can be suppressed, thereby ensuring the filling rate of the positive electrode active material and the capacity of the electrochemical device. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. The larger the tap density, the better, and there is no particular upper limit. In some embodiments, the tap density of the positive electrode active material is less than 4.0 g / cm 3 , less than 3.7g / cm 3 or less than 3.5g / cm 3 When the tap density of the positive electrode active material has the upper limit as described above, a decrease in load characteristics can be suppressed.

[0194] The tap density of the positive electrode active material can be calculated by placing 5 g to 10 g of the positive electrode active material powder in a 10 mL glass measuring cylinder and vibrating the cylinder 200 times with a stroke of 20 mm to obtain the powder packing density (tap density).

[0195] Median particle size (D50)

[0196] When the positive electrode active material particles are primary particles, the median particle size (D50) of the positive electrode active material particles refers to the primary particle size of the positive electrode active material particles. When the primary particles of the positive electrode active material particles aggregate to form secondary particles, the median particle size (D50) of the positive electrode active material particles refers to the secondary particle size of the positive electrode active material particles.

[0197] In some embodiments, the median particle size (D50) of the positive electrode active material particles is greater than 0.3 μm, greater than 0.5 μm, greater than 0.8 μm or greater than 1.0 μm. In some embodiments, the median particle size (D50) of the positive electrode active material particles is less than 30 μm, less than 27 μm, less than 25 μm or less than 22 μm. In some embodiments, the median particle size (D50) of the positive electrode active material particles is within the range composed of any two of the above values. When the median particle size (D50) of the positive electrode active material particles is within the above range, a positive electrode active material with a high tap density can be obtained, which can inhibit the reduction of the performance of the electrochemical device. On the other hand, in the preparation process of the positive electrode of the electrochemical device (that is, when the positive electrode active material, the conductive material and the binder are slurried with a solvent and coated in a thin film), problems such as streaks can be prevented. Here, by mixing two or more positive electrode active materials with different median particle sizes, the filling property during the preparation of the positive electrode can be further improved.

[0198] The median particle size (D50) of the positive electrode active material particles can be measured using a laser diffraction / scattering particle size distribution measuring device: when using LA-920 manufactured by HORIBA as a particle size distribution meter, a 0.1% sodium hexametaphosphate aqueous solution is used as the dispersion medium used in the measurement, and the measurement refractive index is set to 1.24 after 5 minutes of ultrasonic dispersion.

[0199] Average primary particle size

[0200] In the case where the primary particles of the positive electrode active material particles agglomerate to form secondary particles, in some embodiments, the average primary particle size of the positive electrode active material is greater than 0.05 μm, greater than 0.1 μm or greater than 0.5 μm. In some embodiments, the average primary particle size of the positive electrode active material is less than 5 μm, less than 4 μm, less than 3 μm or less than 2 μm. In some embodiments, the average primary particle size of the positive electrode active material is within the range formed by any two of the above values. When the average primary particle size of the positive electrode active material is within the above range, the powder filling property and specific surface area can be ensured, the reduction of battery performance can be suppressed, and appropriate crystallinity can be obtained, thereby ensuring the reversibility of charging and discharging of the electrochemical device.

[0201] The average primary particle size of the positive electrode active material can be obtained by observing the image obtained by scanning electron microscopy (SEM): in the SEM image with a magnification of 10,000 times, for any 50 primary particles, the longest value of the slice obtained by the left and right boundary lines of the primary particles relative to the horizontal straight line is calculated, and the average value is calculated to obtain the average primary particle size.

[0202] Specific surface area (BET)

[0203] In some embodiments, the specific surface area (BET) of the positive electrode active material is greater than 0.1 m 2 / g, greater than 0.2m 2 / g or greater than 0.3m 2 In some embodiments, the specific surface area (BET) of the positive electrode active material is less than 50 m 2 / g, less than 40m 2 / g or less than 30m 2 / g. In some embodiments, the specific surface area (BET) of the positive electrode active material is within the range formed by any two of the above values. When the specific surface area (BET) of the positive electrode active material is within the above range, the performance of the electrochemical device can be ensured, and the positive electrode active material can have good coating properties.

[0204] The specific surface area (BET) of the positive electrode active material can be measured by the following method: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), pre-drying the sample at 150°C for 30 minutes under nitrogen flow, and then using a nitrogen-helium mixed gas with a relative pressure value of nitrogen accurately adjusted to 0.3 relative to atmospheric pressure, the sample is measured by the nitrogen adsorption BET single-point method using the gas flow method.

[0205] Positive electrode conductive material

[0206] There is no limitation on the type of positive electrode conductive material, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; carbon materials such as amorphous carbon such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.

[0207] In some embodiments, the content of the positive electrode conductive material is greater than 0.01%, greater than 0.1%, or greater than 1%, based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode conductive material is less than 10%, less than 8%, or less than 5%, based on the weight of the positive electrode active material layer. When the content of the positive electrode conductive material is within the above range, sufficient conductivity and capacity of the electrochemical device can be ensured.

[0208] Positive electrode binder

[0209] There is no particular restriction on the type of positive electrode binder used in the manufacture of the positive electrode active material layer. In the case of a coating method, any material that can be dissolved or dispersed in the liquid medium used in the manufacture of the electrode can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or their hydrogenates, ethylene-propylene-diene terpolymers (EPDM), Thermoplastic elastomer polymers such as styrene·ethylene·butadiene·ethylene copolymers, styrene·isoprene·styrene block copolymers or their hydrides; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene·vinyl acetate copolymers, propylene·α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene·ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc. The above-mentioned positive electrode binders can be used alone or in any combination.

[0210] In some embodiments, the content of the positive electrode binder is greater than 0.1%, greater than 1%, or greater than 1.5%, based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode binder is less than 10%, less than 8%, less than 5%, or less than 4%, based on the weight of the positive electrode active material layer. When the content of the positive electrode binder is within the above range, the positive electrode can have good conductivity and sufficient mechanical strength, and the capacity of the electrochemical device is guaranteed.

[0211] Solvents

[0212] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, water and mixed media of alcohol and water. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.

[0213] Thickener

[0214] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, a thickener and a styrene-butadiene rubber (SBR) emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.

[0215] In some embodiments, the content of the thickener is greater than 0.1%, greater than 0.2% or greater than 0.3% based on the weight of the positive electrode active material layer. In some embodiments, the content of the thickener is less than 5%, less than 3% or less than 2% based on the weight of the positive electrode active material layer. In some embodiments, the content of the thickener is within the range of any two of the above values ​​based on the weight of the positive electrode active material layer. When the content of the thickener is within the above range, the positive electrode slurry can have good coating properties, and the capacity reduction and resistance increase of the electrochemical device can be suppressed.

[0216] Content of positive electrode active material

[0217] In some embodiments, the content of the positive electrode active material is greater than 80%, greater than 82%, or greater than 84% based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode active material is less than 99% or less than 98% based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode active material is within the range of any two arrays above based on the weight of the positive electrode active material layer. When the content of the positive electrode active material is within the above range, the capacitance of the positive electrode active material in the positive electrode active material layer can be ensured, and the strength of the positive electrode can be maintained.

[0218] Density of the positive electrode active material layer

[0219] The positive electrode active material layer obtained by coating and drying may be compacted by a manual press or a roller press to increase the packing density of the positive electrode active material. In some embodiments, the density of the positive electrode active material layer is greater than 1.5 g / cm 3 , greater than 2g / cm 3 or greater than 2.2g / cm 3 In some embodiments, the density of the positive electrode active material layer is less than 5 g / cm 3 , less than 4.5g / cm 3 or less than 4g / cm 3 In some embodiments, the density of the positive electrode active material layer is within the range formed by any two of the above values. When the density of the positive electrode active material layer is within the above range, the electrochemical device can have good charge and discharge characteristics, while suppressing the increase of resistance.

[0220] Thickness of positive electrode active material layer

[0221] The thickness of the positive electrode active material layer refers to the thickness of the positive electrode active material layer on either side of the positive electrode current collector. In some embodiments, the thickness of the positive electrode active material layer is greater than 10 μm or greater than 20 μm. In some embodiments, the thickness of the positive electrode active material layer is less than 500 μm or less than 450 μm.

[0222] Method for producing positive electrode active material

[0223] The positive electrode active material can be manufactured using a common method for manufacturing inorganic compounds. In order to make a spherical or ellipsoidal positive electrode active material, the following manufacturing method can be used: dissolve or crush the raw material of the transition metal and disperse it in a solvent such as water, adjust the pH while stirring, make a spherical precursor and recover it, dry it as needed, add a Li source such as LiOH, Li2CO3, LiNO3, and sinter it at a high temperature to obtain a positive electrode active material.

[0224] 2. Positive electrode current collector

[0225] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.

[0226] There is no particular restriction on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the form of the positive electrode current collector may include, but is not limited to, metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the form of the positive electrode current collector may include, but is not limited to, carbon plate, carbon film, carbon cylinder, etc. In some embodiments, the positive electrode current collector is a metal foil. In some embodiments, the metal foil is mesh-shaped. The thickness of the metal foil is not particularly limited. In some embodiments, the thickness of the metal foil is greater than 1 μm, greater than 3 μm, or greater than 5 μm. In some embodiments, the thickness of the metal foil is less than 1 mm, less than 100 μm, or less than 50 μm. In some embodiments, the thickness of the metal foil is within the range composed of any two of the above values.

[0227] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode active material layer, the surface of the positive electrode current collector may include a conductive additive. Examples of the conductive additive may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver.

[0228] The thickness ratio of the positive electrode active material layer to the positive electrode current collector refers to the thickness of the single-sided positive electrode active material layer divided by the thickness of the positive electrode current collector, and its value is not particularly limited. In some embodiments, the thickness ratio is less than 50, less than 30, or less than 20. In some embodiments, the thickness ratio is greater than 0.5, greater than 0.8, or greater than 1. In some embodiments, the thickness ratio is within the range of any two of the above values. When the thickness ratio is within the above range, the heat release of the positive electrode current collector during high current density charging and discharging can be suppressed, and the capacity of the electrochemical device can be ensured.

[0229] 3. Method of making positive electrode

[0230] The positive electrode can be made by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector. The manufacture of a positive electrode using a positive electrode active material can be carried out by a conventional method, that is, the positive electrode active material and the binder, as well as the conductive material and the thickener as required, are dry-mixed to form a sheet, and the obtained sheet is pressed onto the positive electrode current collector; or these materials are dissolved or dispersed in a liquid medium to form a slurry, and the slurry is applied to the positive electrode current collector and dried to form a positive electrode active material layer on the current collector, thereby obtaining a positive electrode.

[0231] IV. Isolation membrane

[0232] In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually used by infiltrating the separator.

[0233] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.

[0234] The isolation film may also be a material formed by laminating the above materials, and examples thereof include, but are not limited to, a three-layer isolation film formed by laminating polypropylene, polyethylene, and polypropylene in this order.

[0235] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (e.g., barium sulfate, calcium sulfate, etc.) The form of the inorganic material may include, but is not limited to, granular or fibrous.

[0236] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators may also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with aluminum oxide particles having a particle size of 90% less than 1 μm.

[0237] The thickness of the isolation membrane is arbitrary. In some embodiments, the thickness of the isolation membrane is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the isolation membrane is less than 50 μm, less than 40 μm, or less than 30 μm. In some embodiments, the thickness of the isolation membrane is within the range formed by any two of the above values. When the thickness of the isolation membrane is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the electrochemical device can be ensured.

[0238] When a porous material such as a porous sheet or non-woven fabric is used as an isolation membrane, the porosity of the isolation membrane is arbitrary. In some embodiments, the porosity of the isolation membrane is greater than 10%, greater than 15%, or greater than 20%. In some embodiments, the porosity of the isolation membrane is less than 60%, less than 50%, or less than 45%. In some embodiments, the porosity of the isolation membrane is within the range formed by any two of the above values. When the porosity of the isolation membrane is within the above range, insulation and mechanical strength can be ensured, and membrane resistance can be suppressed, so that the electrochemical device has good safety characteristics.

[0239] The average pore size of the isolation membrane is also arbitrary. In some embodiments, the average pore size of the isolation membrane is less than 0.5 μm or less than 0.2 μm. In some embodiments, the average pore size of the isolation membrane is greater than 0.05 μm. In some embodiments, the average pore size of the isolation membrane is within the range formed by any two of the above values. If the average pore size of the isolation membrane exceeds the above range, short circuit is likely to occur. When the average pore size of the isolation membrane is within the above range, the electrochemical device has good safety characteristics.

[0240] V. Electrochemical Device Components

[0241] The electrochemical device assembly includes an electrode group, a current collecting structure, an outer casing and a protective element.

[0242] Electrode Group

[0243] The electrode group may be any of a laminated structure formed by laminating the above-mentioned positive electrode and the negative electrode with the above-mentioned separator, and a structure formed by spirally winding the above-mentioned positive electrode and the negative electrode with the above-mentioned separator. In some embodiments, the proportion of the mass of the electrode group in the internal volume of the battery (electrode group occupancy) is greater than 40% or greater than 50%. In some embodiments, the electrode group occupancy is less than 90% or less than 80%. In some embodiments, the electrode group occupancy is within the range formed by any two of the above values. When the electrode group occupancy is within the above range, the capacity of the electrochemical device can be ensured, and at the same time, the reduction of characteristics such as repeated charge and discharge performance and high temperature storage associated with the increase in internal pressure can be suppressed.

[0244] Current collection structure

[0245] There is no particular limitation on the current collection structure. In some embodiments, the current collection structure is a structure that reduces the resistance of the wiring portion and the joint portion. When the electrode group is the above-mentioned stacked structure, it is suitable to use a structure formed by bundling the metal core portions of each electrode layer and welding them to the terminal. When the electrode area of ​​a sheet increases, the internal resistance increases, so it is also suitable to set more than two terminals in the electrode to reduce the resistance. When the electrode group is the above-mentioned winding structure, the internal resistance can be reduced by setting more than two lead structures at the positive electrode and the negative electrode respectively, and bundling them at the terminal.

[0246] External shell

[0247] The material of the outer casing is not particularly limited, as long as it is a material that is stable to the electrolyte used. The outer casing can be made of, but not limited to, nickel-plated steel, stainless steel, aluminum or aluminum alloy, magnesium alloy and other metals, or a laminated film of resin and aluminum foil. In some embodiments, the outer casing is a metal or laminated film of aluminum or aluminum alloy.

[0248] The metal outer casing includes, but is not limited to, a packaged closed structure formed by welding metals to each other by laser welding, resistance welding, and ultrasonic welding; or a riveted structure formed by using the above-mentioned metals through a resin gasket. The outer casing using the above-mentioned laminated film includes, but is not limited to, a packaged closed structure formed by thermally bonding resin layers to each other. In order to improve the sealing performance, a resin different from the resin used in the laminated film can also be sandwiched between the above-mentioned resin layers. When the resin layer is thermally bonded to form a closed structure through the collector terminal, due to the bonding between the metal and the resin, a resin with a polar group or a modified resin into which a polar group is introduced can be used as the sandwiched resin. In addition, the shape of the outer casing is also arbitrary, for example, it can be any of cylindrical, square, laminated, button-shaped, large, etc.

[0249] Protection components

[0250] The protection element may be a positive temperature coefficient (PTC) whose resistance increases when abnormal heat is released or excessive current flows, a temperature fuse, a thermistor, or a valve (current cutoff valve) that cuts off the current flowing in the circuit by causing the internal pressure or internal temperature of the battery to rise sharply when abnormal heat is released. The above protection element may be selected to be an element that does not work in normal use of high current, or may be designed in a form that does not cause abnormal heat release or thermal runaway even if the protection element is not present.

[0251] VI. Application

[0252] The electrochemical device of the present application includes any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery or a lithium ion secondary battery.

[0253] The present application further provides an electronic device, which includes the electrochemical device according to the present application.

[0254] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0255] The preparation of lithium-ion batteries is described below by taking lithium-ion batteries as an example and combining specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.

[0256] Example

[0257] The following describes the performance evaluation of the examples and comparative examples of the lithium-ion battery according to the present application.

[0258] 1. Preparation of lithium-ion batteries

[0259] 1. Preparation of negative electrode

[0260] Artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose were mixed with deionized water in a mass ratio of 96%:2%:2%, and stirred evenly to obtain a negative electrode slurry. The negative electrode slurry was coated on a 12 μm current collector. The tensile strength of the negative electrode current collector and the weight per unit area of ​​the negative electrode active material layer were controlled according to the following embodiments or comparative examples. Then, the negative electrode was obtained by drying, cold pressing, cutting, and welding the tabs.

[0261] 2. Preparation of positive electrode

[0262] Lithium cobalt oxide (LiCoO2), conductive material (Super-P) and polyvinylidene fluoride (PVDF) were mixed with N-methylpyrrolidone (NMP) in a mass ratio of 95%:2%:3%, and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on a 12μm aluminum foil, dried, cold pressed, and then cut and welded to the tabs to obtain a positive electrode.

[0263] 3. Preparation of electrolyte

[0264] In a dry argon environment, EC, PC and DEC (weight ratio 1:1:1) were mixed, and LiPF6 was added and mixed evenly to form a basic electrolyte, wherein the concentration of LiPF6 was 1.15 mol / L. Different amounts of additives were added to the basic electrolyte to obtain electrolytes of different embodiments and comparative examples. The abbreviations and names of the components in the electrolyte are shown in the following table:

[0265]

[0266] 4. Preparation of isolation membrane

[0267] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0268] 5. Preparation of lithium-ion batteries

[0269] The obtained positive electrode, separator and negative electrode are wound in order and placed in an outer packaging foil, leaving a liquid injection port. The electrolyte is poured from the liquid injection port, packaged, and then subjected to formation, capacity and other processes to obtain a lithium-ion battery.

[0270] 2. Test Method

[0271] 1. Test method for high temperature storage expansion rate of lithium-ion batteries

[0272] At 25°C, the lithium-ion battery was left to stand for 30 minutes, then charged to 4.45V at a constant current rate of 0.5C, and then charged to 0.05C at a constant voltage rate of 4.45V, left to stand for 5 minutes, and the thickness of the lithium-ion battery was measured. The thickness of the lithium-ion battery was measured again after being stored at 60°C for 21 days. The high-temperature storage expansion rate of the lithium-ion battery was calculated by the following formula:

[0273] High temperature storage expansion ratio = [(thickness after storage - thickness before storage) / thickness before storage] x 100%.

[0274] 2. Test method for cyclic expansion rate of lithium-ion batteries

[0275] At 25°C, the lithium-ion battery was left to stand for 30 minutes, then charged to 4.45V at a constant current rate of 0.5C, and then charged to 0.05C at a constant voltage rate of 4.45V, left to stand for 5 minutes, and the thickness of the lithium-ion battery was measured. The lithium-ion battery was cycled 100 times under the same conditions, and then the thickness of the lithium-ion battery was measured. The cycle expansion rate of the lithium-ion battery was calculated by the following formula:

[0276] Cycle expansion ratio = [(thickness after cycle - thickness before cycle) / thickness before cycle] × 100%.

[0277] 3. Test method for discharge capacity retention rate of lithium-ion batteries

[0278] The lithium-ion battery was discharged at 0.5C constant current to 3.0V, left standing for 5 minutes, then charged at 0.5C constant current to 4.45V, and charged at constant voltage to a cut-off current of 0.05C, left standing for 5 minutes, and then discharged at 0.2C and 5C constant currents to a cut-off voltage of 3.0V. The discharge capacity at 5C was recorded as D1, and the discharge capacity at 0.2C was recorded as D0. The discharge capacity retention rate of the lithium-ion battery at 5C was calculated based on the discharge capacity at 0.2C by the following formula:

[0279] Discharge capacity retention rate = [(D1-D0) / D0] × 100%

[0280] For each embodiment or comparative example, 5 samples were tested and the average value was taken.

[0281] 3. Test Results

[0282] Table 1 shows the effects of the tensile strength of the negative electrode current collector and the weight per unit area of ​​the negative electrode active material layer on the high temperature storage expansion ratio and cycle expansion ratio of the lithium ion battery.

[0283] Table 1

[0284]

[0285]

[0286] “ / ” means that the feature is not added or not available

[0287] The results show that when the tensile strength of the negative electrode collector in the electrochemical device is 400N / mm 2 The weight per unit area of ​​the negative electrode active material layer is 3 mg / cm 2 Up to 12mg / cm 2 When the negative electrode is charged and discharged, the expansion or contraction of the negative electrode caused by the charge and discharge of the electrochemical device is suppressed, which is beneficial to stabilize the structure of the negative electrode active material layer, thereby significantly reducing the high-temperature storage expansion rate and cycle expansion rate of the lithium-ion battery.

[0288] When the negative electrode current collector includes 0.01% to 0.5% of the first metal (silver and / or tin), the high-temperature storage expansion rate and cycle expansion rate of the lithium-ion battery can be further reduced.

[0289] When the tensile strength of the negative electrode current collector is FN / mm 2 When the content a% of the first metal in the negative electrode current collector satisfies 4≤F×a≤200, the high-temperature storage expansion rate and cycle expansion rate of the lithium-ion battery can be further reduced.

[0290] When the tensile strength of the negative electrode current collector is FN / mm 2 The weight per unit area of ​​the negative electrode active material layer is Wmg / cm 2 When 100 / 3≤F / W≤200 is satisfied, the high temperature storage expansion rate and cycle expansion rate of the lithium-ion battery can be further reduced.

[0291] Table 2 shows the density of the negative electrode active material layer Dg / cm 3 Its tensile strength with the negative electrode current collector FN / mm 2 The relationship between the high temperature storage expansion rate and the cycle expansion rate of the lithium ion battery performance is shown in Table 2. The difference between Examples 2-1 to 2-11 and Examples 1-1 and 1-5 is only the parameters listed in Table 2.

[0292] Table 2

[0293]

[0294] The results show that when the negative electrode current collector further includes a first metal (tin and / or silver) or a combination thereof with a rare earth element, the high temperature storage expansion rate and cycle expansion rate of the lithium ion battery can be further reduced. 2 The density of the negative electrode active material layer is Dg / cm 3 (D is 1.4 to 2.0) When 560≤F×D≤1200 is satisfied, the high temperature storage expansion rate and cycle expansion rate of the lithium-ion battery can be further reduced.

[0295] Table 3 further shows the effect of the thickness of the negative electrode current collector and 0.2% endurance on the high temperature storage expansion rate and cycle expansion rate of the lithium ion battery. The difference between Examples 3-1 and 3-4 and Example 1-1 is only the parameters listed in Table 3.

[0296] Table 3

[0297]

[0298]

[0299] As shown in Table 3, the negative electrode current collector may have the following characteristics: 0.2% endurance is 30N / mm2 When the negative electrode current collector has a 0.2% endurance and / or thickness within the above range, it helps to further reduce the high temperature storage expansion rate and cycle expansion rate of the lithium ion battery.

[0300] Table 4 further shows the influence of the reflectivity Ra of the negative electrode active material and the negative electrode active material layer at a wavelength of 550 nm on the high temperature storage expansion rate, cycle expansion rate and discharge capacity retention rate of the lithium ion battery.

[0301] The only difference between Examples 4-1 to 4-6 and Example 1-1 is the parameters listed in Table 4.

[0302] Table 4

[0303]

[0304] The results show that using different negative electrode active materials to make the reflectivity Ra of the negative electrode active material layer at a wavelength of 550nm be 7% to 15% can further reduce the high-temperature storage expansion rate and cycle expansion rate of the lithium-ion battery, and at the same time can significantly improve the discharge capacity retention rate of the lithium-ion battery.

[0305] Table 5 shows the effect of electrolyte components on the high temperature storage expansion rate and cycle expansion rate of lithium ion batteries. The difference between Examples 5-1 to 5-35 and Example 1-1 is only the parameters listed in Table 5.

[0306] Table 5

[0307]

[0308]

[0309] “ / ” means that the feature is not added or not available

[0310] The results show that the tensile strength of the negative electrode current collector is 400N / mm 2 The weight per unit area of ​​the negative electrode active material layer is 3 mg / cm 2 Up to 12mg / cm 2 On the basis of, when the electrolyte contains propionate, an organic compound having a cyano group, lithium difluorophosphate and / or the compound of Formula 1, the high temperature storage expansion rate and cycle expansion rate of the lithium ion battery can be further reduced.

[0311] Table 6 shows the influence of the relationship between the content a% of the first metal in the negative electrode current collector and the content b% of the compound having a cyano group in the electrolyte on the high temperature storage expansion rate and cycle expansion rate of the lithium ion battery. The difference between Examples 6-1 to 6-10 and Example 1-1 is only the parameters listed in Table 6.

[0312] Table 6

[0313]

[0314] The results show that when the content of compounds with cyano groups in the electrolyte is 0.01% to 10%, the high-temperature storage expansion rate and cycle expansion rate of lithium-ion batteries can be further reduced.

[0315] When the content a% of the first metal in the negative electrode current collector and the content b% of the compound having a cyano group in the electrolyte satisfy 1≤b / a≤300, the high temperature storage expansion rate and cycle expansion rate of the lithium ion battery can be further reduced.

[0316] Table 7 shows the content b% of the compound having a cyano group in the electrolyte and the weight per unit area Wmg / cm2 of the negative electrode active material layer. 2 The relationship between the high temperature storage expansion rate and the cycle expansion rate of the lithium-ion battery is shown in Table 7. The difference between Examples 7-1 to 7-6 and Example 1-1 is only the parameters listed in Table 7.

[0317] Table 7

[0318]

[0319]

[0320] The results show that when the content of the cyanide compound in the electrolyte is b% and the weight per unit area of ​​the negative electrode active material layer is Wmg / cm 2 When 0.5≤W / b≤24 is satisfied, the high temperature storage expansion rate and cycle expansion rate of the lithium-ion battery can be further reduced.

[0321] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.

[0322] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. An electrochemical device comprising: A positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, wherein: The tensile strength of the negative electrode current collector is FN / mm 2 , F is 400 or more, The weight per unit area of ​​the negative electrode active material layer is W mg / cm 2 , W is in the range of 3 to 12; The electrolyte comprises at least one of the following compounds: i. Propionate; ii. Compounds having a cyano group; iii. lithium difluorophosphate; or iv. Compounds of formula 1: in: W is L is each independently a single bond or a methylene group, and two Ls in the same ring structure are not simultaneously single bonds; m is 1, 2, 3 or 4; n is 0, 1 or 2. 2 . The electrochemical device according to claim 1 , wherein the negative electrode current collector comprises copper element.

3. The electrochemical device according to claim 1, wherein the negative electrode current collector comprises a first metal, the first metal comprises at least one of silver or tin, and the content of the first metal is a%, based on the weight of the negative electrode current collector, and a is in the range of 0.01 to 0.

5. The electrochemical device according to claim 3 , wherein the negative electrode current collector further comprises at least one rare earth element. 5 . The electrochemical device according to claim 3 , wherein F and a satisfy: 4≤F×a≤200. The electrochemical device according to claim 1 , wherein F and W satisfy: 100 / 3≤F / W≤200.

7. The electrochemical device according to claim 1, wherein the density of the negative electrode active material layer is D g / cm 3 , D is in the range of 1.4 to 2.0, and F and D satisfy: 560≤F×D≤1200.

8. The electrochemical device according to claim 1, wherein the negative electrode current collector has at least one of the following characteristics: 1) The average surface roughness is 0.05μm to 1.5μm; 2) 0.2% endurance is 30N / mm 2 above; 3) The thickness is 1 μm to 100 μm.

9. The electrochemical device according to claim 1, wherein the negative electrode active material layer has at least one of the following characteristics: a) the reflectivity Ra at a wavelength of 550nm is 7% to 15%; b) The porosity Pa is 20% to 40%.

10. The electrochemical device according to claim 1, wherein the compound of Formula 1 comprises at least one of the following compounds: 11 . The electrochemical device according to claim 1 , wherein the content of the compound having a cyano group is b %, based on the weight of the electrolyte, and b is in the range of 0.01 to 10.

12. The electrochemical device according to claim 11, wherein the negative electrode current collector comprises a first metal, the first metal includes at least one of silver or tin, and the content of the first metal is a%, based on the weight of the negative electrode current collector, a is in the range of 0.01 to 0.5 and 1≤b / a≤300.

13. The electrochemical device according to claim 11, wherein W and b satisfy: 0.5≤W / b≤24.

14. An electronic device comprising the electrochemical device according to any one of claims 1 to 13.